2015
DOI: 10.3389/fpsyg.2015.01730
|View full text |Cite
|
Sign up to set email alerts
|

People’s Financial Choice Depends on their Previous Task Success or Failure

Abstract: Existing knowledge about the impact of the experience prior to financial choices has been limited almost exclusively to single risky choices. Moreover, the results obtained in these studies have not been entirely consistent. For example, some studies suggested that the experience of success makes people more willing to take a risk, while other studies led to the opposite conclusions. The results of the two experimental studies presented in this paper provide evidence for the hypothesis that the experience of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
(72 reference statements)
1
13
0
Order By: Relevance
“…We believe that decreased propensity to take financial risk in the non-financial victim condition is in line with other studies showing that individuals who watched a sad movie clip 6 We base this assumptions on the results of our previous pilot studies (Sekscinska 2015) showing that for Poles quotas equal PLN 500 (approximately $130)and above are perceived to be meaningful. Fig.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…We believe that decreased propensity to take financial risk in the non-financial victim condition is in line with other studies showing that individuals who watched a sad movie clip 6 We base this assumptions on the results of our previous pilot studies (Sekscinska 2015) showing that for Poles quotas equal PLN 500 (approximately $130)and above are perceived to be meaningful. Fig.…”
Section: Discussionsupporting
confidence: 76%
“…One of possible explanations might be the amount of money the participants decided about. While in the present studies risky choices concerned amounts of money pretested to be meaningful (Sekscinska 2015), in the studies conducted so far, risky choices involved very small quotas. In a study of Mishra et al (2015) participants performed a Choice Task, in which they decided between CAD$3 for sure and a risky option that ranged from 80% probability of receiving CAD$3.75 to 10% probability of receiving CAD$30 (which in 2015 was an equivalent of approximately $21).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…They focused on different decision domains like the financial, social, or health domains. The findings showed that, contrary to classical decision theories, risky decisions are affected by various factors like framing (e.g., Tversky and Kahneman, 1981), the source of the probability information (Hertwig et al, 2004), any previous experience (e.g., Sekścińska, 2015a), the decision maker's individual traits (e.g., Campbell et al, 2004), or even the activation of a different social role (Sekścińska et al, 2016). This signifies that decisions made in different domains (even when they are made concurrently) should not be described by the same and stable utility function.…”
Section: Introductionmentioning
confidence: 82%
“…Both RFQ scales exhibited good internal reliability (α = 0.73 for the Promotion scale; α = 0.080 for the Prevention scale; Higgins et al, 2001). The propensity to make financial choices was measured with one question tool in which the participants were asked to select one category of financial activity (consuming, saving, or investing) on which they would spend a hypothetical PLN 10,000 (as used in previous studies—Sekścińska, 2015a; Sekścińska et al, 2016). The tool also included information on the meaning of consuming, saving, and investing in the context of the study: consuming in the sense of spending money on products or services; saving meaning keeping the money in a nonprofitable (or almost nonprofitable) form without any risk of loss, for instance, a deposit in a noninterest-bearing bank account.…”
Section: Methodsmentioning
confidence: 99%